Development of vertical and horizontal vortex type separator for subsea application - Kopey, B. V.; Kryvonozhko, T. A. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2015)
The paper offers the vortex type separator for the four-phase mixture separation in traditional system of separation and redesign or improvement of the vortex type horizontal separator with gravity filter for minimizing the dimension and mass of the separator, collecting sand in a separate tank, enhancing mechanical properties of a multiphase twin-screw pump material by decreasing the hydro-abrasive wear. The mathematical model for the proposed construction of the separator is also elaborated.